2009
DOI: 10.1038/ng.483
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of ulcerative colitis identifies three new susceptibility loci, including the HNF4A region

Abstract: Ulcerative colitis (UC) is a common form of inflammatory bowel disease with a complex aetiology. As part of the Wellcome Trust Case Control Consortium 2, we performed a genomewide association scan for UC in 2361 cases and 5417 controls. Loci showing evidence of association at P < 1 × 10 −5 were followed up by genotyping in an independent set of 2321 cases and 4818 controls. We find genome-wide significant evidence of association at three new loci, each containing at least one biologically relevant candidate ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
258
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(265 citation statements)
references
References 36 publications
7
258
0
Order By: Relevance
“…This finding was replicated later by independent UC association studies (11,32). Additionally, the Wellcome Trust Case Control Consortium 2 (WTCCC 2) study of 15 complex disorders and traits reported a GWA scan in UC This study replicated the number of loci previously reported by Fisher et al (5) to be associated ECM1 with UC (33). Ankylosing spondylitis, like UC, is a chronic inflammatory disease, and there is a frequent clinical overlap between them.…”
Section: Discussionsupporting
confidence: 77%
“…This finding was replicated later by independent UC association studies (11,32). Additionally, the Wellcome Trust Case Control Consortium 2 (WTCCC 2) study of 15 complex disorders and traits reported a GWA scan in UC This study replicated the number of loci previously reported by Fisher et al (5) to be associated ECM1 with UC (33). Ankylosing spondylitis, like UC, is a chronic inflammatory disease, and there is a frequent clinical overlap between them.…”
Section: Discussionsupporting
confidence: 77%
“…The methods and quality control have been described in greater detail elsewhere 22 as part of the WTCCC2 project. 23 In total, 2329 genotyped individuals were available for whom phenotype information at age 12 were also available.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
“…Genome-wide association studies have identified genes contributing to susceptibility to Crohn's disease and ulcerative colitis. Many of these susceptibility loci play a role in immune responses to microbial signalling and processing (11) as well as epithelial barrier integrity (12,13) . Germ-free animal models of colitis indicate that the microbiota drives inflammation in genetically susceptible hosts (14) .…”
Section: Dysbiosis In Inflammatory Bowel Diseasesmentioning
confidence: 99%